The Impact of Tourism Events on Destination Image Enhancement and Tourist Loyalty - Safira Atmadya Putri; Boge Triatmanto; Sofia Martinez (Lembaga Penelitian dan Pendidikan, 2026)
Tourism events have become a strategic tool in enhancing destination competitiveness by strengthening destination image and fostering tourist loyalty. This study aims to analyze the impact of tourism events on destination image enhancement and its implication for tourist loyalty. A quantitative research approach was employed using a survey method involving 210 tourists who attended cultural and sport tourism events. Data were analyzed using Structural Equation Modeling (SEM). The findings reveal that tourism events have a significant positive effect on destination image. Furthermore, destination image significantly influences tourist loyalty, both directly and indirectly through tourist satisfaction. Event quality and memorable experiences play a crucial mediating role in shaping perceptions and behavioral intentions. This study confirms that well-organized tourism events contribute not only to short-term visitation but also to long-term destination branding and loyalty formation. The results provide practical implications for destination managers to strategically design event portfolios that enhance image and strengthen visitor attachment.